PREVENTION AND CONTROL OF THE TAX EVASION IMPACT ON ROMANIAN ECONOMY - Raluca Andreea TRANDAFIR (Management Intercultural, 2015)

(untitled)
Time of occurrence of tax evasion is closely linked even to social developments, this social phenomenon has emerged and evolved at the same time with the company. Since tax evasion is a phenomenon particularly harmful and despicable paradoxically, it has unfortunately been a negative and unintended consequence, with directions of development and different incidents in any country, regardless of size, level of development or form power organization. In Romania, the underground economy is strong because it is determined by the size of the phenomenon of crime in the economic and financial (dirty money), a phenomenon characterized by a very high level of "financial engineering" made in the privatization, investment, financial institutions - banks and the use of public funds. Thus, effective tools are triggered by conversion and diversion of capital flows in order to remove it from licit financial circuit.